Reoperation after surgical treatment for benign prostatic hyperplasia: a systematic review - He, Weixiang; Ding, Ting; Niu, Zhiping; Hao, Chunlin; Li, Chengbin; Xu, Zhicheng; Jing, Yuming; Qin, Weijun (Frontiers in Endocrinology, 2023)
Context Surgical treatment is important for male lower urinary tract symptom (LUTS) management, but there are few reviews of the risks of reoperation. Objective To systematically evaluate the current evidence regarding the reoperation rates of surgical treatment for LUTS in accordance with current recommendations and guidelines. Evidence acquisition Eligible studies published up to July 2023, were searched for in the PubMed® (National Library of Medicine, Bethesda, MD, USA), Embase® (Elsevier, Amsterdam, the Netherlands), and Web of Science™ (Clarivate™, Philadelphia, PA, USA) databases. STATA® (StataCorp LP, College Station, TX, USA) software was used to conduct the meta-analysis. Random-effects models were used to calculate the pooled incidences (PIs) of reoperation and the 95% confidence intervals (CIs). Evidence synthesis A total of 119 studies with 130,106 patients were included. The reoperation rate of transurethral resection of the prostate (TURP) at 1, 2, 3, and 5 years was 4.0%, 5.0%, 6.0%, and 7.7%, respectively. The reoperation rate of plasma kinetic loop resection of the prostate (PKRP) at 1, 2, 3, and 5 years was 3.5%, 3.6%, 5.7%, and 6.6%, respectively. The reoperation rate of holmium laser enucleation of the prostate (HoLEP) at 1, 2, 3, and 5 years was 2.4%, 3.3%, 5.4%, and 6.6%, respectively. The reoperation rate of photoselective vaporization of the prostate (PVP) at 1, 2, 3, and 5 years was 3.3%, 4.1%, 6.7%, and 7.1%, respectively. The reoperation rate of surgery with AquaBeam® at 1, 2, 3, and 5 years was 2.6%, 3.1%, 3.0%, and 4.1%, respectively. The reoperation rate of prostatic artery embolization (PAE) at 1, 2, 3, and 5 years was 12.2%, 20.0%, 26.4%, and 23.8%, respectively. The reoperation rate of transurethral microwave thermotherapy (TUMT) at 1, 2, 3, and 5 years was 9.9%, 19.9%, 23.3%, and 31.2%, respectively. The reoperation rate of transurethral incision of the prostate (TUIP) at 5 years was 13.4%. The reoperation rate of open prostatectomy (OP) at 1 and 5 years was 1.3% and 4.4%, respectively. The reoperation rate of thulium laser enucleation of the prostate (ThuLEP) at 1, 2, and 5 years was 3.7%, 7.7%, and 8.4%, respectively. Conclusion Our results summarized the reoperation rates of 10 surgical procedures over follow-up durations of 1, 2, 3, and 5 years, which could provide reference for urologists and LUTS patients. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42023445780.